2005
DOI: 10.1007/s10450-005-5912-9
|View full text |Cite
|
Sign up to set email alerts
|

Confined Water in Mesoporous MCM-41 and Nanoporous AlPO4-5: Structure and Dynamics

Abstract: Confined water presents unusual properties in comparison with other sorbate species. First of all, the sorption isotherm is of type III, even in the microporous confinement range (Ø < 20Å). Whatever the pore diameter, water sorption phenomenon looks like the so-called capillary condensation phase transition. Our results clearly valid such an expected behaviour in the mesoporous confinement range (20Å < Ø < 40Å). The water confined phase is a liquid phase characterized by a short range order and a high translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…In recent years the effect of confinement on properties of "materials" has been investigated including general aspects, [10] but of course also considering liquids [11] and these especially in context with confined water properties. [12][13][14][15] One possible way to investigate confined water molecule assemblies systematically is by trapping them in structurally well defined and differently sized as well as functionalized nanosized capsule cavities. This is possible with soluble spherical porous capsules of the type [{pentagonal unit} 12 {metal linker unit} 30 [16a,b] which are stable in solution under welldefined conditions, while the pores can, as an important aspect, be closed in a stepwise manner.…”
mentioning
confidence: 99%
“…In recent years the effect of confinement on properties of "materials" has been investigated including general aspects, [10] but of course also considering liquids [11] and these especially in context with confined water properties. [12][13][14][15] One possible way to investigate confined water molecule assemblies systematically is by trapping them in structurally well defined and differently sized as well as functionalized nanosized capsule cavities. This is possible with soluble spherical porous capsules of the type [{pentagonal unit} 12 {metal linker unit} 30 [16a,b] which are stable in solution under welldefined conditions, while the pores can, as an important aspect, be closed in a stepwise manner.…”
mentioning
confidence: 99%
“…Therefore, at low temperature the pore would appear more uniformly filled while the walls are less wet and water molecules are arranged in a cubic-ice-like structure. 44 The analogies found between the patterns of the two systems suggest that the features observed for the structure factor at Q ≈ 1.5 Å −1 are related in our case to intra-cluster organization of water molecules within the polymeric matrix. This means, such molecular reorganization would not be directly connected to the above described structural evolution at the inter-cluster and polymer nano-domains levels.…”
Section: Structural Featuresmentioning
confidence: 52%
“…We note that very similar qualitative features and temperature dependence have been reported for water confined in mesoporous MCM-41. 44,45 A combined study of neutron diffraction and empirical potential structure refinement (EPSR) simulations 45 suggested that the mesoscopic arrangement of water molecules in the pore could change as a result of the modified water-water and watersubstrate interactions. Upon cooling, the H-bonds between water molecules would be strengthened, while those between water and the wall atoms become weaker.…”
Section: Structural Featuresmentioning
confidence: 99%
“…In the case of AlPO 4 -5, a vertical uptake is observed around P/P 0 = 0.3 without an explicit hysteresis. 46 Thus, we have several questions about water vapor adsorption on the hydrophobic nanoporous solids: What is adsorption hysteresis? Why does hydrophobic porous carbon exhibit hydrophilic behavior?…”
Section: Accommodative Filling Of Water Molecules In Hydrophobic Spacesmentioning
confidence: 99%